2013
DOI: 10.1152/ajpregu.00544.2012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme and the tumor microenvironment: mechanisms beyond angiogenesis

Abstract: Okwan-Duodu D, Landry J, Shen XZ, Diaz R. Angiotensin-converting enzyme and the tumor microenvironment: mechanisms beyond angiogenesis. Am J Physiol Regul Integr Comp Physiol 305: R205-R215, 2013. First published June 5, 2013 doi:10.1152/ajpregu.00544.2012.-The renin angiotensin system (RAS) is a network of enzymes and peptides that coalesce primarily on the angiotensin II type 1 receptor (AT 1R) to induce cell proliferation, angiogenesis, fibrosis, and blood pressure control. Angiotensin-converting enzyme (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 158 publications
(175 reference statements)
0
27
0
2
Order By: Relevance
“…While ACEis act inhibiting the conversion of angiotensin I to angiotensin II, ARBs act on the receptors of this hormone. The protective effect of ACEis has been demonstrated in animal models of solid cancers [40,41], but certain authors have also found that the chronic treatment with ACEis might produce the accumulation of some peptides with protumor effect, such as bradykinin, substance P, and Nacetyl-seryl-aspartyl-lysyl-proline [42]. ARBs, in turn, selectively block the angiotensin II type 1 receptors, responsible for vasoconstriction, cell growth, and sympathetic activation and in this way exerts their potential antineoplastic effect, maintaining the beneficial effects of angiotensin II type 2-receptor stimulation (vasodilatory and antiproliferative action mediated via the kinin system) [21,37].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While ACEis act inhibiting the conversion of angiotensin I to angiotensin II, ARBs act on the receptors of this hormone. The protective effect of ACEis has been demonstrated in animal models of solid cancers [40,41], but certain authors have also found that the chronic treatment with ACEis might produce the accumulation of some peptides with protumor effect, such as bradykinin, substance P, and Nacetyl-seryl-aspartyl-lysyl-proline [42]. ARBs, in turn, selectively block the angiotensin II type 1 receptors, responsible for vasoconstriction, cell growth, and sympathetic activation and in this way exerts their potential antineoplastic effect, maintaining the beneficial effects of angiotensin II type 2-receptor stimulation (vasodilatory and antiproliferative action mediated via the kinin system) [21,37].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the reality is much more challenging to monitor because of the large degree of fluctuation in abundance and localization of these tumor-secreted proteins, especially in the early stage of tumor development and/or metastasis (5, 6). As such, it seems feasible that we might take advantage of the fact that secreted proteases/peptidases in the tumor microenvironment generate proteolytic products, also referred to as “circulating peptides”, and these are continuously released into interstitial fluid, lymph, eventually making their way into the bloodstream (7). Consequently, blood samples can provide ample information about the body, “coded” in the patterns and quantity of these peptides (8).…”
Section: Introductionmentioning
confidence: 99%
“…Support for this hypothesis also comes from pre-clinical studies demonstrating that oxidative damage, from both cardiac etiologies [30] and radiation therapy [31], dysregulates the ACE/angiotensin pathway, leading to elevated levels of TGFB and VEGF, molecules essential to the pathogenesis of fibrosis and poor organ function; ABT is able to modulate these pathways and lead to decrease late side effects in vivo [32]. Overall, these pre-clinical and clinical studies provide multiple levels of support to our findings that ABT is associated with lower risk of SRN after intracranial SRS.…”
Section: Discussionmentioning
confidence: 99%